Operação do conjunto bomba centrífuga, motor de indução trifásico e conversor de freqüência visando a eficiência no uso da energia elétrica - Schmidlin Júnior, Celso Rogério (2006)
This work aims to experimentally quantify, in LAMOTRIZ, the reduction of the active power required by the drive of a centrifugal pump that opts for the operation according to the outflow reduction method by speed variation instead the one that uses strangulation valve. Moreover, aims to develop a mathematical model that is capable to previously determine the consumption of electric energy of a pumping system that operates according to any one of these two methods of outflow reduction.